Constitution and laws of the Cherokee Nation - Boudinot, W. P. (William P.); Ross, Daniel H. (Daniel Hicks); Scales, J. A. (Joseph A.) (LLMC-digital (Series), 1875)
This 1875 facsimile of the laws of the Cherokee Nation includes the tribes' full constitution. Readers will recognize many of the laws and articles, as the constitution was based on that of the United States. For instance, the Cherokee Nation constitution states that the power of this Government shall be divided into three distinct departments; the Legislative, the Executive, and Judicial.